Indigenous sovereignty in research and epistemic justice: Truth telling through research - Raglan Maddox; Melody E. Morton Ninomiya (Global Public Health)
Indigenous ways of knowing, being and doing are based on embodied sovereignty, relationality and countless generations of knowledge sharing. We call for epistemic justice in which Indigenous knowledge systems are recognised and valued in research-related contexts. We draw attention to how colonial knowledge systems silence, delegitimise and devalue specific knowers and ways of knowing, being and doing – through truth telling. This includes (1) the extent to which educational systems, research, practices, decisions, and reported outcomes are whitewashed – a process of structural and systemic discrimination, racism, and exclusion that actively alters or omits Indigenous and non-Euro-Western contributions and perspectives to fit Euro-Western norms and (2) whitewashed and racialised logic in scientific research that claims to be open, collaborative and transparent. Whitewashing not only obscures the history and contributions of Indigenous peoples and communities but also actively reinforces systemic biases and inequities. We assert the need for epistemic justice in public health research. Epistemic justice calls for Indigenous sovereignty and self-determination to be made visible. It may involve on how colonial policies, protocols, and regulations are connected to everyday lived inequities of Indigenous communities, families and individuals. Ultimately, epistemic justice is inherent to Indigenous peoples’ health and wellness, self-determination and sovereignty.